Desenvolvimento de visibilidade na cadeia de suprimentos: um modelo conceitual - Gallo, Igor Sant'Ana (2020)
The increasing dynamism and environment complexity demand more responsive supply chains, but the technology development allowed companies to take full advantage of supply chain visibility to cope with sudden changes. To develop visibility, it is necessary to identify which information the company should exchange and what factors might impact its value. This research proposes the term visibility dimension to refer to the type of information that can be exchanged to improve supply chain visibility and influential characteristics to organization’s social and operating characteristics that can influence the value of a certain visibility dimension. Through the lenses of Contingency Theory and Social Capital Theory, this research presents how influential characteristics impact the development of supply chain visibility. The fit between the visibility dimensions and categories of influential characteristics is defined as visibility configurations. To do so, a systematic literature review was performed to identify the main dimensions, categories of characteristics, and links between a type of information and an influential characteristic. The second part of this project followed a Q-sort method to test if the characteristics and types of information were correctly labeled into the categories of characteristics and visibility dimensions, respectively. The results showed that the visibility dimensions had a high agreement between the judges, but the characteristics part did not. Although the second part of the questionnaire presented some problems, the characteristics that had low agreement could be verified through one of the theoretical lenses or past researches on the topic, so the items were theoretically validated. This research presents contributions to both practitioners and researchers. For practitioners, this research provided an actionable framework to develop visibility and provided guidelines on how to determine which visibility dimension should be developed. For the literature, this research provided two contributions. First, a formal definition of visibility dimensions, a synthesis of the approaches to develop visibility available in the literature. Second, a theory grounded analysis on how influential characteristics impact the development of supply chain visibility and propose the first version of the visibility configurations that might explain the conflicting results regarding some influential characteristics. This research was exploratory, so future researches might validate the configurations proposed and consider the impacts the categories of characteristics have on each other. Researchers should also consider the impact of the visibility dimensions on the categories to provide a more accurate picture of how influential characteristics impact the development of visibility.